Adaptive systems in control and signal processing 1992 - Dugard, L.; M'Saad, M.; Landau, Yean D.; International Federation of Automatic Control. Technical Committee on Applications; IFAC Symposium on Adaptive Systems in Control and Signal Processing (4th : 1992 : Grenoble, France) (Oxford : Pergamon, 1993)
14